Social appearance anxiety and body checking behavior in the relationship between social media addiction and depressive symptoms among college students - Xiaochen Wang; Yanan Wang; Shufei Yang; Zhen Li; Chang Fu (Frontiers in Psychiatry)
BackgroundThe relationship between social media addiction and depressive symptoms has been extensively studied; however, the underlying mechanisms remain unexplored. This study examined the mediating roles of social appearance anxiety and body checking behaviors in this relationship. This research aims to address the gap in understanding how social media addiction influences mental health, particularly among college students.MethodsData from 1,456 students recruited from three universities in Shandong, China, were analyzed using structural equation modeling. Demographic characteristics of the participants were collected and assessed for social appearance anxiety, body checking behaviors, social media addiction, and depressive symptoms.ResultsThe prevalence of depressive symptoms was 13.9% in the study sample. Social appearance anxiety, body checking behavior, and social media addiction were significantly and positively correlated with depressive symptoms (r = 0.367 - 0.519, p < 0.001). Social media addiction directly and positively predicted depressive symptoms with a direct effect value of 0.173. Furthermore, social appearance anxiety and body checking behavior played independent and serial multiple mediating roles in the association between social media addiction and depressive symptoms, with indirect effect values of 0.193, 0.035, and 0.235, respectively.ConclusionSocial media addiction is a significant risk factor contributing to depressive symptoms among college students. This study provides new insight into the mechanisms underlying the relationship between social media addiction and mental health, with implications for global mental health interventions. Specifically, the negative impact of social media addiction is mediated by social appearance anxiety and body checking behavior. These findings suggest that school administrators and policymakers should develop targeted interventions to reduce social media addiction among college students and prioritize providing psychological support to alleviate social appearance anxiety and promote a healthy body image. By addressing these factors, this research contributes to a broader understanding of mental health challenges in the digital age.